Will Happiness-Trainings Make Us Happier? A Research Synthesis Using an Online Findings-Archive - Bergsma, Ad; Buijt, Ivonne; Veenhoven, Ruut (Frontiers in Psychology, 2020)
Most people want to be happy and many look out for opportunities to achieve a more satisfying life. Following a happiness training is an option, but the effectiveness of such training is being questioned. In this research synthesis we assessed: (1) whether happiness training techniques add to the happiness of their users, (2) how much happiness training techniques add to happiness, (3) how long the effect of happiness training lasts, (4) what kinds of training techniques work best, and (5) what types of groups of people profit from taking happiness training. We took stock of the available research and found 61 reports of effect studies on training techniques, which together yielded 179 findings. These findings are available in an online “findings archive,” the World Database of Happiness. Using links to this source allows us to condense information in tabular overviews, while providing the reader with access to much detail. Happiness training techniques seem to do what they are designed to do: 96% of the studies showed a gain in happiness post intervention and at follow-up, about half of the positive results were statistically significant. Studies with cross-sectional designs and studies that used control groups showed more mixed results. The average effect of happiness training was approximately 5% of the scale range. We conclude that taking a form of happiness training is advisable for individuals looking for a more satisfying life. Since happier workers tend to be more productive, organizations would be wise to provide such training techniques for their workforce.